كفاية رأس المال في المصرف التجاري السوري - بيطار منى; الكواس فارس طه (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إنَّ تطبيق معايير بازل II يعتبر من المواضيع الحديثة نسبياً، وتحظى باهتمام كبير من المنظمات المالية والمصارف في الكثير من الدول المتقدمة والنامية. ومن الطبيعي أن يكون سبب هذا الاهتمام هو الرغبة في الاستفادة من المنافع المتعددة التي تقدمها معايير بازل للمصارف في مجال قياس وإدارة المخاطر المصرفية وتحقيق الرقابة عليها واتخاذ القرارات الإدارية الملائمة. يهدف البحث إلى إيضاح كيفية تطبيق معيار بازلII لكفاية رأس المال في المصرف التجاري السوري، من خلال التعريف بلجنة بازل ومعايير بازل I ومعايير بازلII ، ثم تقديم دراسة تطبيقية على المصرف التجاري السوري لبيان كيفية تطبيق معيار بازلII لكفاية رأس المال وأثر متطلبات كفاية رأس المال الجديدة على المحفظة الائتمانية للمصرف التجاري السوري واستبدال الأصول ذات الأوزان الترجيحية الأعلى بأصول ذات أوزان ترجيحية أقل. وقد تمَّ التوصل إلى أنَّ المصرف يحتفظ بنسبة عالية من رأس المال تفوق ما هو مطلوب في معيار بازل II لكفاية رأس المال، وبالتالي يجب على المصرف البحث عن استثمارات جديدة لتوظيف الفائض من رأسماله. Using standards of Basel II in the banking sector is a relatively new subject, which concerns financial organizations and banks in a lot of developed and developing countries. Naturally, the reason for this interest is the desire to benefit from the various advantages which Basel II standards offers in measuring and management the banking risks, the supervision and taking the suitable administrative decisions. This research aims to explain the applying of capital adequacy standard of Basel II in Commercial Bank of Syria, through defining by Basel Committee, standards of Basel I and standards of Basel II, then offers a practical study on the Commercial Bank of Syria in order to show how Commercial Bank of Syria apply the capital adequacy standard of Basel II and the effect of the new capital adequacy requirements under the Basel II on its portfolio, to alter its assets away from heavily weighted risk assets into unweighted assets. In the research end, we found that Commercial Bank of Syria has high rate of capital more than capital rate in Basel II for Capital Adequacy, so the bank has to look for new investments in order to invest his surplus capital.